Factor structure of the Cognitive Fusion Questionnaire in university students from Lima - Valencia, Pablo (2019)
Background: Cognitive fusion is a core concept in Acceptance and Commitment Therapy. The Cognitive Fusion Questionnaire (CFQ) was developed as a unidimensional measure that would overcome the limitations of previous endeavors. Method: The current study analyzed the factor structure of the CFQ in Peruvian undergraduates (n = 450, 53% female). It also examined whether such structure was invariant between males and females. Results: Data supported the hypothesized unidimensionality, as well as strict invariance. No difference was found between males and females regarding the latent means of cognitive fusion. Reliability of the scale was high (ω = .916). Conclusion:Suggestions are made that future studies a) include other measures alongside the CFQ, b) examine the quality of the CFQ at different levels of the construct, and c) test whether or not different measures of cognitive (de)fusion measure the same construct.